MHD model results of solar wind interaction with Mars and comparison with MAVEN plasma observations. Issue 21 (5th November 2015) - Ma, Y. J.; Russell, C. T.; Fang, X.; Dong, Y.; Nagy, A. F.; Toth, G.; Halekas, J. S.; Connerney, J. E. P.; Espley, J. R.; Mahaffy, P. R.; Benna, M.; McFadden, J. P.; et al.
Abstract: The Mars Atmosphere and Volatile EvolutioN mission (MAVEN), launched on 18 November 2013, is now in its primary science phase, orbiting Mars with a 4.5 h period. In this study, we use a time‐dependent MHD model to interpret plasma observations made by MAVEN particle and field instruments. Detailed comparisons between the model and the relevant plasma observations from MAVEN are presented for an entire Mars rotation under relatively quiet solar wind conditions. Through comparison along MAVEN orbits, we find that the time‐dependent multispecies single‐fluid MHD model is able to reproduce the main features of the plasma environment around Mars. Using the model results, we find that photoionization beyond the terminator is the dominant ion source as compared with day‐night transport in maintaining the nightside ionosphere. Model results also show that both the time‐varying solar wind conditions and the continuously rotating crustal field work together to control the ion escape variation with time. Key Points: A time‐dependent MHD model is used to interpret plasma observations made by MAVEN Photoionization beyond the terminator is the dominant ion source for the nightside ionosphere Both solar wind conditions and the rotating crustal field control the ion escape from Mars